Sustainability Reporting in the EU-27: The Impact of National ESG Ecosystems and Organizational Implications - Alexandru Avram; Georgiana Maria Lungu; Costin Daniel Avram; Luminița Popescu; Daniel Tobă; Iulia-Cristina Ciurea (Amfiteatru Economic)
Sustainability reporting is a vital element that enables stakeholders to discern how companies comply with social, environmental, and governance regulations while assessing sustainable development. This study examines the national context that influences corporate sustainability reporting, emphasising the interplay between macrolevel ESG economic conditions and firm-level disclosures mandated by frameworks such as the Corporate Sustainability Reporting Directive (CSRD). While previous studies focused on organisational and concept-level analysis, the originality of this study lies in the direct evaluation of national ESG-economic ecosystems on the preparedness of EU member states for sustainability reporting under the new directive. A macroeconomic analysis of the EU-27 member states was performed using key ESG and economic indicators, with the principal component analysis generating a composite index of national performance. Additionally, the clustering of K-means revealed different regional profiles that reflect differences in ESG economic metrics. These findings have important implications, as countries with stronger macro indicators encourage environments that facilitate the adoption of advanced reporting methods, while countries facing economic and institutional challenges may require targeted interventions to improve transparency and compliance. This approach provides valuable information for policymakers and investors, emphasising the systemic links between national conditions and effective sustainability reporting at the organisational level